PTH-167 Clinico-pathological characteristics of patients under barrett's surveillance at a tertiary referral centre. (22nd June 2015) - Farrell, M; Bornschein, J; Zeki, S; DiPietro, M; Fitzgerald, RC
Abstract : Introduction: Barrett's oesophagus is a premalignant condition for the development of oesophageal adenocarcinoma. Guidelines have been established to guide which patients should be included in endoscopic surveillances schemes. We evaluated the clinico-pathological characteristics of patients under surveillance at our tertiary referral centre including a large local practice, and compared patients with dysplastic lesions to those with non-dysplastic appearance of the Barrett's mucosa. Method: Clinico-pathological data has been retrieved from a prospective Barrett's database for 551 patients (73.3% male, mean age 63.0+/-11.55 years), including patients with non-dysplastic Barrett's and with different stages of dysplasia and intramucosal cancer. Patients without histological confirmation of Barrett's mucosa and patients with more advanced adenocarcinomas were excluded from this analysis. Categorical data was compared using Fisher's exact test, group comparison of metric data by the Mann-Whitney U- and the student's t-test for age. Correlation analysis was done by Spearman's rank correlation test. Results: The study cohort comprised 227 patients with non-dysplastic Barrett's (NDB), 110 classified as indefinite for dysplasia (ID), 146 with low grade dysplasia (LGD), 29 with high grade dysplasia (HGD), and 39 with intramucosal cancer (IMC). The mean number of consecutive endoscopies was higher for patients with dysplasia compared to NDB patients (NDB: 4.00, ID: 4.77, LGD 5.48, HGD: 8.62, IMC: 8.92; p < 0.001). However, patients with HGD and IMC had a mean of 1.72 and 0.87 procedures prior to diagnosis, respectively. Patients with HGD and IMC are more likely to present with a lesion at first endoscopy (NDB: 9.3%, ID: 10.3%, LGD 9.0%, HGD: 24.1%, IMC: 41.1%; p < 0.001). In the case of HGD these are mainly ulcers (17.2%) and nodules (6.9%), whereas for IMC these were mainly nodules (38.5%). The maximum extent of the Barrett's mucosa (M-level) correlated positively with the patients' age (r = 0.312, p < 0.001), length of a present hiatus hernia (r = 0.278, p = 0.001) and the degree of pathological changes (r = 0.198, p < 0.001). Patients with NDB showed more often oesophagitis than patients with dysplastic lesions (21.6% vs 8.4%, p < 0.001), but in similar proportion to patients with ID (22.7%, p = 0.888). Conclusion: The type of lesion at first presentation varies with the degree of the histopathological changes. IMC is shows more nodular appearance whereas presence of an ulcer indicates HGD. Oesophagitis is more often present at non-dysplastic stages. This needs to be confirmed in a prospective multicentre cohort. Disclosure of interest: None Declared.